2022
DOI: 10.3991/ijet.v17i17.29403
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Model for e-Learning Activities Based on Digital Incentives Within the Context of COVID-19 and its Effectiveness in Developing Meta-Cognitive Thinking Among Higher Education Students

Abstract: The COVID-19 pandemic has created many challenges that have affected the efficiency of practicing e-learning activities, and therefore the current study was directed towards developing a model for e-learning activities based on digital incentives, especially gamification-based incentives such as points, badges, levels, and leader boards, to stimulate meta-cognitive thinking processes for higher education students during the pandemic. The quasi-experimental approach was used to compare the two study groups, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Moreover, the result of this systematic literature review also showed students' creativity should be encouraged in designing an education platform. However, several studies (Su and Cheng, 2013;Topirceanu, 2017;Alsulaimani, 2022;Nousiainen et al, 2021;Gilyazova & Zamoshchanskii, 2020) have highlighted how gamification aids student creativity by developing and implementing several activities that enhance students social behaviors, logical reasoning, critical thinking abilities, the development of cognitive abilities, the improvement of concentration and attention levels, the development of complex thinking and strategic planning abilities, the support of multidisciplinary learning, and the enhancement of motivation for learning. Additionally, Zafar et al (2018) and Alsulaimani et al (2022) explained that the overall academic performance of students improved in gamified learning systems because gamification allows students to learn at one's personal momentum, observe, and control learning activities owning it to the fact that they are eager to complete each subtask in order to receive digital incentives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the result of this systematic literature review also showed students' creativity should be encouraged in designing an education platform. However, several studies (Su and Cheng, 2013;Topirceanu, 2017;Alsulaimani, 2022;Nousiainen et al, 2021;Gilyazova & Zamoshchanskii, 2020) have highlighted how gamification aids student creativity by developing and implementing several activities that enhance students social behaviors, logical reasoning, critical thinking abilities, the development of cognitive abilities, the improvement of concentration and attention levels, the development of complex thinking and strategic planning abilities, the support of multidisciplinary learning, and the enhancement of motivation for learning. Additionally, Zafar et al (2018) and Alsulaimani et al (2022) explained that the overall academic performance of students improved in gamified learning systems because gamification allows students to learn at one's personal momentum, observe, and control learning activities owning it to the fact that they are eager to complete each subtask in order to receive digital incentives.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested numerous learners practicing misconceptions of skill while considering in addition such misconceptions have huge results for the techniques understudies select when they regulate and manage their knowledge. Thus, the study carried out by Parcel (Alsulaimani, 2022) focused on determining meta-cognitive awareness and its effect on the academic achievement. She did work on a sample of one hundred and forty-seven fifth graders and collected data through an online instructional training with meta-cognitive prompts.…”
Section: Literature Reviewmentioning
confidence: 99%